A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Heilongjiang, China - Zhang, Da-Peng; Li, Shao-Hua; Yin, Zhan (Zootaxa, 2020)
The genus Haplotropis Saussure, 1888 belongs to family Pamphagidae, superfamily Acridioidea. It contains five species: Haplotropis brunneriana Saussure, 1888; Haplotropis xiai Ye, Shi & Li 2016; Haplotropis zhuoluensis Ye, Shi & Li 2016; Haplotropis aqiensis Zhang, Lin et Yin, 2018 and Haplotropis shandongensis Zhang, Yin et Liu, 2019 distributed mainly in Amur River region of Asia and China only (Saussure, 1888; Bey-Bienko et Mishchenko, 1951; Otte, 1994; Yin, Shi et Yin, 1996; Storozhenko & Paik, 2011; Yin et al, 2014; Dong et al, 2015; Ye et al, 2016; Zhang et al, 2017; Zhang et al, 2018; Zhang et al, 2019; Cigliano et al, 2019). A new species Haplotropis heiheensis sp. nov. is described in this paper. The new species is similar to Haplotropis aqiensis Zhang, Lin et Yin, 2018, but differs from latter by Krauss’ organ of male without ramified keel; tegmine narrower, length 2.4 times width; cercus of male gently tapering at apical half part; minimum width 1.4 times length in mesosternum and epiphallus with 36 spikes. Type specimens are deposited in the College of Plant Protection, Shandong Agricultural University, Taian, Shandong, China.